TRADISI RATIBAN DI DESA PANDANSARI : BENTUK SYUKUR KEPADA SANG PENCIPTA ATAS HASIL LIMPAHAN ALAM - Revadila Safiqoh Yamil Agustin (JURNAL ILMU BUDAYA, 2025)
Culture in Indonesia is very diverse and is often found in Java, such as the traditional thanksgiving ceremony which is carried out to give thanks to the creator. In Pandansari Village, there is a ratiban ritual, which is a form of the community’s request to always be looked after and eliminate the difficulties they are experiencing as well as a form of gratitude to Allah for the abundance of nature. The objectives of this research are, 1) How is the Ratiban Tradition implemented in Pandansari Village ; 2) What is the background for implementing the Ratiban tradition ; 3) What is the meaning and function of holding the Ratiban tradition, as well as the impact on the local community. The benefit of this research is to find out how to preserve Ratiban and to know that Indonesia is rich in culture. The method used in this research is descriptive qualitative.